Variasi Konsentrasi Maltodekstrin Terhadap Karakteristik Fisik dan Aktivitas Antibakteri Orally Disintegrating Film Ekstrak Daun Pecut Kuda (Stachytarpheta jamaicencis L.) - Putri, Yola Desnera; Ledianasari, Ledianasari; Aziza, Farradiba Nur (JFIOnline | Print ISSN 1412-1107 | e-ISSN 2355-696X, 2022)
Abstract: Orally dissolving film (ODF) preparations are a new invention that allows drugs to be used more conveniently than other oral solid preparations without the need for drinking water. Porterweed (Stachytarpheta jamaicencis L) is one of herbal medicine that can be developed into an Orally Disintegrating Film (ODF) preparation with providing fast disintegration time and convenience comsumption especially for patients who have difficulty swallowing tablets. Main component in ODF preparations is polymer. Combination of HPMC K100M and maltodextrin produce good physical characteristics. The research was aimed to determine the influence of variations concentration 3.5 grams, 4.5 grams and 5.5 grams of maltodextrin on the physical characteristic of ODF containing porterweed extract. Stages of research carried out the formulation of basis and preparations continued with physical evaluated and antibacterical activity. To ensure that the resulting ODF preparations are ideal, evaluation tests need to be carried out including organoleptic, pH of the preparations, average weight, thickness, swelling index, disintegration time, tensile strength, percent elongation, and antibacterial activity. The best physical characterictis evaluation is formula 2 of ODF porterweed extract (Stachytarpheta jamaicencis L) containing 4.5 grams of maltodextrin with pH surface 6.75 ± 0.025, average weight 0.0499 ± 0.0001 g, thickness 0.0997 ± 0.002 mm,  swelling index in 15;30; and 45 sec. are 257.49 ± 0.244%; 322.46 ± 0.202%; and 403.21 ± 0.197%, disintegration time in 54 sec., tensile strength 12.67± 0.374 MPa, percent elongation 20% and have strong category of antibacterial ability against Staphylococcus aureus in 11.43 ± 1.401 mm.